Netherlands Yearbook of International Law 2017 Shifting Forms and Levels of Cooperation in International Economic Law: Structural Developments in Trade, Investment and Financial Regulation (Netherlands Yearbook of International Law,, 2018)
This Volume of the Netherlands Yearbook of International Law explores emerging trends and key developments in international economic law. It examines shifts in the levels of cooperation (from multilateral to plurilateral, regional or bilateral-or vice versa), and shifts in the forms of cooperation (new types of actors and instruments). These trends are analysed both from a conceptual and a practical perspective, with contributions addressing drivers for change, historical perspectives, future developments, and evolutions in specific policy fields. While a focus on international economic law may certainly not tell the whole story in relation to shifts in levels and forms of international cooperation, it does allow for a more detailed analysis of some of the important trends we currently witness. The Netherlands Yearbook of International Law was first published in 1970. It offers a forum for the publication of scholarly articles in a varying thematic area of public international law. .